Bestimmung des Zeitverhaltes einer induktiv beheizten Wirbelschicht und deren Einflussgrößen. Issue 3 (27th November 2012) - Stresing, Antje; Mörl, Lothar; Khaidurova, Aleksandra; Jacob, Michael; Walther, Klaus
<x xml:space="preserve">Abstract</x> A new contactless method for supplying energy to a fluidized bed is presented. An electromagnetic field supplies power to electro conductive inert particles. This technique is characterized by high energy densities and fast heating rates as well as high efficiency. It is essential in the metal processing industry. The experimental results show that the advantages of inductive heating can also be used for fluidized bed applications. The key aspect here is the determination of the time response and its parameters.